Does Cloud Computing offer small to medium sized businesses in the Agri-Trading industry strong enough advantages to warrant adoption? A case study on Dalmark Grain - Madelil, Nitin George (2011)
The objective of this research is to evaluate the potential of cloud computing for small to medium sized businesses in the Agri-Trading industry. The research uses Dalmark Grain as the focal point for analysis and recommendations. Dalmark Grain provides an ideal case example for the purpose of this research as its core business application – the trading platform - is dated and the management is currently contemplating a major upgrade. Given the investment associated with a typical upgrade, the management is keen to evaluate every possible opportunity especially if there are financial and performance related advantages. However, the research does not limit itself to merely evaluating the possibility of a cloud deployment based on the current workloads and business processes at Dalmark Grain. Integral to the decision on whether or not to migrate is the question of what additional features and functionality the new IT system ought to offer the business. Therefore, the research also provides a critical analysis of the key business processes and recommendations on how they can be streamlined as well as a market research to understand customer expectations. Clearly, a key factor in whether or not a cloud deployment is feasible for the Agri-Trading industry is readiness of vendors to roll out cloud based solutions. For this reason, both Touchstone Group and Cultura – the two main vendors for the industry – were also interviewed. Interestingly, both vendors have solutions built on the Microsoft Dynamics platform for which Microsoft has recently announced a cloud roadmap. The research does not make any recommendation on which vendor would be more suitable for the business and the management at Dalmark Grain is advised to engage in further due-diligence to arrive at a decision. Finally, the research will reveal that cloud based deployments are indeed a viable option for businesses like Dalmark Grain that are forced to upgrade their IT systems and are sensitive to the capital investment associated with the traditional IT model. However, the decision to migrate is not without risk and hence the paper concludes with a comprehensive risk assessment.